Endocrine factors involved in divergence and dominant follicle in cattle - Hernández Martínez, Ingris Yohana; Pacheco López, Jenny Johanna; Castro Santos, Ana Paula; de Souza Sales, José Nelio (Spei Domus, 2020)
The purpose of this article is to provide the reader with knowledge about the growth relationship between the future dominant follicle FD, the subordinate follicle (FS) and the intraovarian factors that influence follicular divergence in cattle. Development. This review begins by presenting the importance of follicular divergence, when a significant difference is observed in the growth rate between the first two follicles. Thereafter, the aspects that influence this divergence are covered: presence of the corpus luteum (CL), its relationship with the dominant follicle (DF) and plasma progesterone concentrations (P4), in addition to the endocrine and molecular factors related to the follicular divergence. It is concluded that as more in-depth research is carried out, new factors that influence this process are discovered.
Keywords: follicular divergence; dominant follicle; progesterone; corpus luteum